In Silico Study of Avocado (Persea americana Mill.) Seed Compounds Against PBP2a Receptor on Staphylococcus aureus - Kusuma, Meike Tyas; Susilowati, Retno (Future Science, 2018)
The nosocomial infection causes 1,4 million mortality every day in the world. International Nosocomial Infection Control Consortium (INICC) data shows that 84,4% nosocomial infection is caused by S. aureus that can cause skin infection. Avocado (P. americana) seed has been reported as an antibacterial agent and used for dermatological applications. This research was aimed to know the potential of antibacterial activity of ethanolic extract of avocado seed in silico study. The in silico test used molecular docking method with PyRx software between PBP2a as receptor and phytochemical compounds in avocado seed as a ligand. The result showed that rutin compound had the best potential to bind PBP2a (binding affinity: -18,2 kcal/mol). Thus, phytochemical active compounds in avocado seed can be recommended as an antibacterial drug and can increase the number of fibroblast cells caused by S. aureus.